Direct sequencing of a disulfide-linked peptide with electrospray ionization tandem mass spectrometry. Issue 8 (6th March 2015) - Li, Gongyu; Pei, Jiying; Yin, Yue; Huang, Guangming
Abstract : Enhanced corona discharge was employed for in-spray dissociation of disulfide bonds, facilitating disulfide-containing peptide sequencing with ESI-MS/MS. Abstract : Dissociation of disulfide is normally mandatory prior to disulfide peptide sequencing via electrospray ionization collision induced dissociation mass spectrometry (ESI-CID-MS). Herein, a facile method for directly sequencing intact disulfide peptides was proposed. The basic principles involved were electrolyte-enhanced corona discharge in ESI and the following oxidative cleavage reaction.